Német-Ausztria keresztény-konzervatív gondolkodói és válaszaik a gazdasági-társadalmi válságperiódusra : 1918-1938 - Zachar, Péter Krisztián (Közép-Európai Közlemények, 2012)
The present economic crisis did not only exert a serious influence on the economic, production, service and social systems of Western democracies, but also generated a scientific interest in the past crisis periods and their solutions. The Hungarian social and economic history research did not pay necessary attention to the not totalitarian efforts of the interwar period aimed at reforming the state, society and economy till now. This study tries to present the theories based on holistic views of the 1930’s. The suggestion of solution based on conservative thoughts and especially the social teach of the Holy See intended to overcome the crisis by strengthening the community instead of maintaining the individualist society having start to fall apart. The new estate style social and economic organizing model put often under the same heading with corporatism started its winning course especially after the Great Depression. It seemed that the state of vocational order may assist in solving the political and economic crisis and eliminating the lacks of democracy and of capitalism organizing. The study presents two trends of the vocational order conception. The first one is based on social instruction of Roman Catholic Church, which – especially following Johannes Messner – suggested to build a new social and economic order, which is based on subsidiarity and gives free play for democratic elements as well. The concept of the other trend, the universalism however had radically anti-democratic elements. After Othmar Spann’s views it constituted a concept of the autoriter-carismatic state, and leaned to cooperate even with the national socialism for reaching its goal: eliminating the liberalism and „partyocracy”. The author emphasizes in his summary that the Messner-trend did not cease to exist even after the Second World War: the social market economy based on concordance and cooperation between social actors instead of class battle is a descendant of this view in many respects.